Influence of anti-sclerostin monoclonal antibody in the repair of post-extraction sockets of ovariectomized rats - Marcantonio, Camila Chierici [UNESP]; Perles, Gabriel Henrique [UNESP]; Lopes, Maria Eduarda Scordamaia [UNESP]; Soares, Lélio Fernando Ferreira [UNESP]; da Costa, Paulo Inácio [UNESP]; Cerri, Paulo Sergio [UNESP]; Cirelli, Joni Augusto [UNESP] (Elsevier, 2024)
Objective: This study assessed the impact of an anti-sclerostin monoclonal antibody (Scl-Ab)-based osteoporosis drug on the post-extraction alveolar repair of ovariectomized rats. Design: Fifteen female rats were randomly distributed into three groups: CTR (healthy animals), OST (osteoporosis induced by ovariectomy), and OST+Scl-Ab (osteoporosis induction followed by Scl-Ab treatment). Ovariectomy or sham surgery was performed 30 days before baseline, and Scl-Ab or a vehicle was administered accordingly in the groups. After seven days, all rats underwent the first lower molar extraction and were euthanized 15 days later. Computed microtomography, histological analysis, and collagen content measurement were performed on post-extraction sockets and intact mandibular and maxillary bone areas. Results: Microtomographic analyses of the sockets and mandibles did not reveal significant differences between groups on bone morphometric parameters (p > 0.05), while maxillary bone analyses resulted in better maintenance of bone architecture in OST+Scl-Ab, compared to OST (p < 0.05). Descriptive histological analysis and polarization microscopy indicated better post-extraction socket repair characteristics and collagen content in OST+Scl-Ab compared to OST (p < 0.05). Conclusions: Scl-Ab-based medication did not accelerate alveolar bone formation but exhibited better post-extraction repair characteristics, and collagen content compared to ovariectomized animals only.
Keywords: Antibodies; Osteoporosis; Romosozumab; Tooth Extraction; Tooth Socket